2020
DOI: 10.14715/cmb/2020.66.5.29
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of melatonin against the effects of different doses of caffeine on the fetus

Abstract: Skeletal system and some organs development changes in rat fetuses with 30 and 60 mg/kg caffeine and melatonin's (10 mg/kg) protective role against rat fetuses were investigated. Groups (n = 4) were formed as Control, LDC, HDC, LDC+melatonin, HDC+melatonin and melatonin. Fetuses were taken by cesarean section and stained using dual skeletal staining method and FESEM. TRAP and AP immune-reactivity concentrations were calculated. Oxidative stress and inflammatory markers were also measured by liver, bone and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recently, Yılmaz et al clearly demonstrated powerful antioxidant and a protective role for MEL (10 mg/kg bw daily i.p.) against delayed ossi cation in Wistar Albino rat fetuses caused by the use of 60 mg/kg bw daily CAF during pregnancy [15]. More recently, Zhang et al also observed IUGR and maternal immune dysfunction in their study in which they administered CAF by gavage in a volume of 0 (control), 5, 20, and 80 mg/kg bw daily from the 6th day of pregnancy to lactation using CAF dissolved in water [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yılmaz et al clearly demonstrated powerful antioxidant and a protective role for MEL (10 mg/kg bw daily i.p.) against delayed ossi cation in Wistar Albino rat fetuses caused by the use of 60 mg/kg bw daily CAF during pregnancy [15]. More recently, Zhang et al also observed IUGR and maternal immune dysfunction in their study in which they administered CAF by gavage in a volume of 0 (control), 5, 20, and 80 mg/kg bw daily from the 6th day of pregnancy to lactation using CAF dissolved in water [16].…”
Section: Discussionmentioning
confidence: 99%
“…CAF can easily cross both the blood-brain barrier and the placental barrier [1,2,4,11,12]. Studies have reported that caffeine mixed with the drinking water of pregnant animals passes to the fetus [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The images of the dyed fetuses placed on millimeter paper were recorded with a Nikon (5700) camera under a stereomicroscope. Finally, the images transferred to the computer were measured using the ImageJ program (https://imagej.nih.gov/ij/download.html) to measure the cartilaginous and ossification areas on the bones (Yılmaz et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the images transferred to the computer were measured using the ImageJ program (https://imagej.nih.gov/ij/download.html) to measure the cartilaginous and ossification areas on the bones (Yılmaz et al, 2020).…”
Section: Anesthesia and Tissue Samplingmentioning
confidence: 99%
See 1 more Smart Citation